Soil chemical attributes restricting grain yield in Oxisols under no-tillage system - Corassa, Geomar Mateus; Santi, Antônio Luís; Silva, Vanderlei Rodrigues da; Baron, Felipe Arthur; Reimche, Geovane Boschmann; Fioresi, Dejales; Della Flora, Diandra Pinto (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to identify soil chemical attributes restricting grain yield in Oxisols under the no-tillage system, using directed soil sampling. High, medium, and low yield zones were defined in two agricultural fields using historical yield data of several crops. The yield zones were defined based on the harvest maps of the following crops: corn in 2008/2009, white oat in 2009, and corn in 2012/2013 in field I, with 117.70 ha; and corn in 2009/2010, soybean in 2010/2011, and wheat in 2012 in field II, with 107.30 ha. Soil sampling points were georeferenced in each yield zone, where samples were collected at eight soil depths, spaced 0.05 m apart, totaling 80 variables. Low yields were associated with low cation exchange capacity, low phosphorus and organic matter contents, and high clay content. In both studied fields, the highest organic matter content in the subsurface layers was the main indicator of high yield. Soil sampling considering yield zones is an efficient strategy to identify chemical attributes restricting grain yield and also allows guiding more precise site-specific interventions.